2019
DOI: 10.1038/s41467-019-11169-x
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen peroxide release by bacteria suppresses inflammasome-dependent innate immunity

Abstract: Hydrogen peroxide (H 2 O 2 ) has a major function in host-microbial interactions. Although most studies have focused on the endogenous H 2 O 2 produced by immune cells to kill microbes, bacteria can also produce H 2 O 2 . How microbial H 2 O 2 influences the dynamics of host-microbial interactions is unclear. Here we show that H … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
88
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(88 citation statements)
references
References 69 publications
(92 reference statements)
0
88
0
Order By: Relevance
“…The oxidized mitochondrial DNA binds to NLRP3, promotes NLRP3 inflammasome assembly and activates the NLRP3 inflammasome [25]. Although a low level of ROS promotes NLRP3 inflammasome activation, a recent study demonstrated that a high level of ROS generated by Streptococcus pneumonia infection inhibited the NLRP3 inflammasome through the oxidation of the inflammasome components ASC and caspases [30]. We found that although 4-HAB increased mitochondrial ROS production ( Figure 2B), it significantly reduced mitochondrial integrity loss induced by MSU crystals (Figure 2A).…”
Section: Discussionmentioning
confidence: 99%
“…The oxidized mitochondrial DNA binds to NLRP3, promotes NLRP3 inflammasome assembly and activates the NLRP3 inflammasome [25]. Although a low level of ROS promotes NLRP3 inflammasome activation, a recent study demonstrated that a high level of ROS generated by Streptococcus pneumonia infection inhibited the NLRP3 inflammasome through the oxidation of the inflammasome components ASC and caspases [30]. We found that although 4-HAB increased mitochondrial ROS production ( Figure 2B), it significantly reduced mitochondrial integrity loss induced by MSU crystals (Figure 2A).…”
Section: Discussionmentioning
confidence: 99%
“…For example, bacteria such as Streptococcus spp. can restrain inflammasome activation by producing hydrogen peroxide, which in turn dampens bacterial clearance from host cells 28 .…”
Section: Pathogen-derived Activating Signalsmentioning
confidence: 99%
“…Detection of the processed forms of IL-1b and caspase-1 was highly delayed and remained undetectable until 12 h post infection. However, the ratio of processed IL-1b and caspase-1 to their precursors was still very low (100). In contrast, spxB-mutant strain, which lacked H 2 O 2 production, showed an intrinsically increased capacity to activate the inflammasome.…”
Section: Role Of Nlrp3 Inflammasome In Pneumococcal Infectionsmentioning
confidence: 96%
“…In contrast to PLY, only one study investigated the pneumococci-derived H 2 O 2 and inflammasome interplay. By utilizing mouse bone marrow-derived macrophages (mBMDMs), Ertmann and Gekara have shown that mBMDMs infected with pneumococci accumulate large amounts of pro-IL-1b and procaspase-1 (100). Detection of the processed forms of IL-1b and caspase-1 was highly delayed and remained undetectable until 12 h post infection.…”
Section: Role Of Nlrp3 Inflammasome In Pneumococcal Infectionsmentioning
confidence: 99%